Les services en santé mentale pour les jeunes francophones de la région d’Ottawa - Audet, Marie-Pier; Drolet, Marie (Reflets, 2014)

Francophone seniors in Ontario: A health portrait - Bouchard, Louise; Makvandi, E.; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, University of Ottawa, 2014)

Les aînés francophones de l’Ontario : un portrait de santé. - Bouchard, Louise; Makvandi, Ewa; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, Université d'Ottawa, 2014)

The health of the Francophone population aged 65 and over in Ontario. A region-by-region portrait based on the Canadian community health survey (CCHS) - Bouchard, Louise; Makvandi, Ewa; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario & University of Ottawa, 2014)

Francophone men and women in Ontario: A health portrait - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario & University of Ottawa, 2014)

Les hommes et les femmes francophones en Ontario : un portrait de leur santé - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario et Université d’Ottawa, 2014)

La trajectoire des services sociaux et de santé d’aînés atteints d’une démence vivant en contexte francophone minoritaire : un engagement de multiples piliers durant une navigation complexe - Carbonneau, Corine; Drolet, Marie (Reflets, 2014)

Are there mental health differences between Francophone and non-Francophone populations in Manitoba? - Chartier, Mariette Jeanne; Finlayson, Gregory; Prior, Heather; McGowan, Kari-Lynne; Chen, Hui; Walld, Randy; De Rocquigny, Janelle (The Canadian Journal of Psychiatry, 2014)
Objective: Francophones may experience poorer health due to social status, cultural differences in lifestyle and attitudes, and language barriers to health care. Our study sought to compare mental health indicators between Francophones and non-Francophones living in the province of Manitoba. Methods: Two populations were used: one from administrative datasets housed at the Manitoba Centre for Health Policy and the other from representative survey samples. The administrative datasets contained data from physician billings, hospitalizations, prescription drug use, education, and social services use, and surveys included indicators on language variables and on self-rated health. Results: Outside urban areas, Francophones had lower rates of diagnosed substance use disorder (rate ratio [RR] = 0.80; 95% CI 0.68 to 0.95) and of suicide and suicide attempts (RR = 0.59; 95% CI 0.43 to 0.79), compared with non-Francophones, but no differences were found between the groups across the province in rates of diagnosed mood disorders, anxiety disorders, dementia, or any mental disorders after adjusting for age, sex, and geographic area. When surveyed, Francophones were less likely than non-Francophones to report that their mental health was excellent, very good, or good (66.9%, compared with 74.2%). Conclusions: The discrepancy in how Francophones view their mental health and their rates of diagnosed mental disorders may be related to health seeking behaviours in the Francophone population. Community and government agencies should try to improve the mental health of this population through mental health promotion and by addressing language and cultural barriers to health services.

Quand le manque d’accès aux services en français revictimise les femmes victimes de violence conjugale et leurs enfants - Lapierre, Simon; Coderre, Cécile; Côté, sabelle; Garceau, Marie-Luce; Bourassa, Chantal (Reflets, 2014)
Cet article s’appuie sur les résultats d’une recherche réalisée en Ontario et au Nouveau-Brunswick, visant à documenter l’accès aux services en français pour les femmes francophones victimes de violence conjugale et pour leurs enfants. S’appuyant sur les résultats de la première phase d’une recherche-action réalisée en partenariat avec des chercheuses universitaires et des milieux communautaires, les données démontrent que ces femmes sont confrontées à des réalités particulières et que les lacunes dans l’accès aux services en français compromettent leur bien-être, leur santé et leur sécurité. Ces lacunes ont également des impacts sur le bien-être, la santé et la sécurité de leurs enfants. Considérant ces impacts, le manque d’accès aux services en français peut être perçu comme une forme de revictimisation des femmes. Mots-clés : services en français, violence conjugale, violence faite aux femmes, enfants exposés à la violence conjugale, santé des femmes, sécurité des femmes, santé des enfants, sécurité des enfants

La représentation sociale de la dépression et l’accès aux services de santé mentale des jeunes francophones canadiens en contexte minoritaire - Negura, Lilian; Moreau, Nicolas; Boutin, Émilie (Penser les liens entre santé mentale et société : les voies de la recherche en sciences sociales, 2014)

Favoriser le rétablissement dans sa langue. Orientation en santé mentale en français. Version révisée - Société Santé en français (Version révisée, 2014)